Layanan Perbankan BSI Mobile dan Perbandingannya dengan BRImo - Romdhon, Muhammad Rizqi (Sekolah Tinggi Agama Islam Nurul Iman Bogor, 2023)
This research was conducted with the aim of knowing what forms of mobile banking services are available at BSI and in comparison with mobile banking applications at BRI. This study uses a type of qualitative research. This research is descriptive in nature. This research was also carried out through library research. Based on the research that has been done, it can be concluded that the banking services provided by BSI Mobile include banking services in the form of raising and channeling funds, religious social services, banking services, and non-banking services. BRImo has more service features than BSI Mobile, along with an attractive interface system and an easier page switching system. The advantages and conveniences, as well as features that suit customer needs, will attract customers to use them more than others.